2007
DOI: 10.1111/j.1524-475x.2006.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 inhibition of keloid fibroblast migration, contraction, and transforming growth factor (TGF)‐β1–induced collagen synthesis

Abstract: Keloid formation has been linked to aberrant fibroblast activity, exacerbated by growth factors and inflammatory mediators. Prostaglandin E2 (PGE2), synthesized from arachidonic acid by cyclooxygenases (COX) and synthases (PGES), acts as both an inflammatory mediator and fibroblast modulator. Although PGE2 has known antifibrotic effects in the lower airway, its role in dermal fibrosis in general, and keloid formation in particular, remains unclear. This study focused on: (1) the effects of PGE2 on keloid fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 57 publications
7
95
0
Order By: Relevance
“…It was previously proposed that keloid formation may result from inflammation arising from the secretion of proinflammatory mediators and the abnormal response to other inflammatory signals mediated by keloid fibroblasts (12). In accordance with this hypothesis, Chen et al (24) and Messadi et al (25) demonstrated that ~15% of the genes, the most important being proinflammatory factors, such as IL-1α, IL-1β, IL-6 and TNF-α, were upregulated in keloid fibroblasts.…”
Section: Proposed Hypothesis For the Cause Of Keloid Formationsupporting
confidence: 60%
See 2 more Smart Citations
“…It was previously proposed that keloid formation may result from inflammation arising from the secretion of proinflammatory mediators and the abnormal response to other inflammatory signals mediated by keloid fibroblasts (12). In accordance with this hypothesis, Chen et al (24) and Messadi et al (25) demonstrated that ~15% of the genes, the most important being proinflammatory factors, such as IL-1α, IL-1β, IL-6 and TNF-α, were upregulated in keloid fibroblasts.…”
Section: Proposed Hypothesis For the Cause Of Keloid Formationsupporting
confidence: 60%
“…By using gene chip technology, Chen et al (24) and Messadi et al (19) discovered that ~15% of genes in keloid fibroblasts, the most important being proinflammatory factors, were upregulated, suggesting that keloid fibroblasts are crucial in the occurrence of chronic inflammation. It was proposed that keloid formation may be caused by inflammation arising from the abnormal secretion of proinflammatory mediators and irregular response to other inflammatory signals mediated by keloid fibroblasts (12). It was also proven that, as a special form of wound healing, keloids exhibit characteristics similar to the long-lasting inflammatory responses, immune abnormalities and invasive growth characteristics of tumors (31,32).…”
Section: Chronic Inflammation In Keloidsmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, it was suggested that inflammatory granulation tissue formation was caused by fibroblastic stimulation accelerated by COX-2 26) in ill-fitting denture. Regarding the relevance of COX-2 and fibrosis, decreased COX-2 activation and PGE2 levels during tissue repair were associated with increased fibrosis and poor repair outcomes in the lung 27,28) . From the above results, in matured fibrous type, the transition from inflammatory to fibrous tissue type was thought to have been caused by decreased COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, keloid is included in the spectrum of fibroproliferative disorders and commonly affects the ears, it has been suggested that keloid scarring is caused by an inability to stop the wound healing process and abnormal response to inflammation by fibroblasts [63,64]. Scar is densely populated by inflammatory cells, which release fibrogenic factors such as transforming growth factor (TGF)-β1 and -β2.…”
Section: Aberrant Healing Of the Cartilagementioning
confidence: 99%